2024
DOI: 10.2967/jnumed.123.266183
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preclinical Evaluation, and Clinical Translation of68Ga-FAPI-LM3, a Heterobivalent Molecule for PET Imaging of Nasopharyngeal Carcinoma

Liang Zhao,
Yizhen Pang,
Jianyang Fang
et al.

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…This possibility suggests the need for further research to assess the effectiveness of various imaging probes in detecting pulmonary fibrosis, potentially expanding the available diagnostic tools for this disease. Our previous study confirmed the dual-targeting capability of FAPI-LM3 against FAP and SSTR2 in tumor tissues, 12 demonstrating their enhanced uptake and prolonged retention in nasopharyngeal carcinoma (showing positive FAP and SSTR2 expression). This groundwork set the stage for potential future applications in radionuclide internal irradiation therapy for advanced nasopharyngeal carcinoma using 177 Lulabeled compounds.…”
Section: ■ Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…This possibility suggests the need for further research to assess the effectiveness of various imaging probes in detecting pulmonary fibrosis, potentially expanding the available diagnostic tools for this disease. Our previous study confirmed the dual-targeting capability of FAPI-LM3 against FAP and SSTR2 in tumor tissues, 12 demonstrating their enhanced uptake and prolonged retention in nasopharyngeal carcinoma (showing positive FAP and SSTR2 expression). This groundwork set the stage for potential future applications in radionuclide internal irradiation therapy for advanced nasopharyngeal carcinoma using 177 Lulabeled compounds.…”
Section: ■ Resultssupporting
confidence: 82%
“…For heterobivalent probes to be effective, it is crucial that each binding motif retains its biological activity, utilizing a multivalent effect to enhance receptor availability and consequently fibrotic lesion uptake. , This strategy highlights the superiority of heterobivalent molecules over their monomeric counterparts. Various small heterobivalent molecules, including FAPI-PSMA, FAPI-RGD, and BBN-PSMA, exhibit increased tracer uptake in tumors, demonstrating the effectiveness of the dual-targeting approach. ,, Moreover, considering the association of integrin α v β 3 with pulmonary fibrosis, other heterobivalent probes such as FAPI-RGD, which targets integrin α v β 3 and FAP, could potentially detect pulmonary fibrosis. This possibility suggests the need for further research to assess the effectiveness of various imaging probes in detecting pulmonary fibrosis, potentially expanding the available diagnostic tools for this disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations